Grainyhead-like Transcription Factors in Craniofacial Development. (October 2017) - Carpinelli, M.R.; de Vries, M.E.; Jane, S.M.; Dworkin, S.
Craniofacial development in vertebrates involves the coordinated growth, migration, and fusion of several facial prominences during embryogenesis, processes governed by strict genetic and molecular controls. A failure in any of the precise spatiotemporal sequences of events leading to prominence fusion often leads to anomalous facial, skull, and jaw formation—conditions termed craniofacial defects (CFDs). Affecting approximately 0.1% to 0.3% of live births, CFDs are a highly heterogeneous class of developmental anomalies, which are often underpinned by genetic mutations. Therefore, identifying novel disease-causing mutations in genes that regulate craniofacial development is a critical prerequisite to develop new preventive or therapeutic measures. The Grainyhead-like ( GRHL ) transcription factors are one such gene family, performing evolutionarily conserved roles in craniofacial patterning. The antecedent member of this family, Drosophila grainyhead ( grh ), is required for head skeleton development in fruit flies, loss or mutation of Grhl family members in mouse and zebrafish models leads to defects of both maxilla and mandible, and recently, mutations in human GRHL3 have been shown to cause or contribute to both syndromic (Van Der Woude syndrome) and nonsyndromic palatal clefts. In this review, we summarize the current knowledge regarding the craniofacial-specific function of the Grainyhead-like family in multiple model species, identify some of the major target genes regulated by the Grhl transcription factors in craniofacial patterning, and, by examining animal models, draw inferences as to how these data will inform the likely roles of GRHL factors in human CFDs comprising palatal clefting. By understanding the molecular networks regulated by Grhl2 and Grhl3 target genes in other systems, we can propose likely pathways that mediate the effects of these transcription factors in human palatogenesis.